FACTORS CONTRIBUTING TO THE PREVALENCE OF DENTAL CARIES AMONG ADULT (18-30) YEARS POPULATION IN NDEJJE HEALTH CENTRE IV, WAKISO DISTRICT – UGANDA - Nalubega , Suubi Mariam; Okwany, Jimmy (Student’s Journal of Health Research Africa, 2023)
Objective: The purpose of this study was to identify factors contributing to the prevalence of dental caries among adults in Ndejje Health Center IV, Wakiso District. Method: A descriptive cross-sectional hospital-based study was conducted at the dental clinic and with both quantitative and qualitative approaches as the research design was conducted at Ndejje HCIV in Wakiso District in February. Altogether 85 respondents were taken and the respondents were men and women between 18-30 years who attended a dental clinic at the facility. Findings: More than half of the respondents 64% did not seek dental care in the past 6 months. , majority of the respondents 89% regarded it important to have regular dental visits, and the majority, of the respondents 87%, ascribed to the notion that dental diseases can be treated in the hospital but could not go when the need arises. The study revealed that more than half of respondents 53% brush their teeth once a day whereas only 20% brush after every meal and only 29.5% brush twice. Conclusions: The research has reflected less motivation and awareness of dental caries, making people more likely to risk developing caries. All the patients in the present study were informed of their estimated caries risk profile and were encouraged to improve their oral Socioeconomic status, educational level, and poor oral hygiene practices were associated factors for dental caries. Recommendations : Adequate policy guidelines for the supply and uptake of Dental health services in all health facilities in Ndejje HCIV. Streamlining the implementation of Oral health care by integrating it with other health programs. The Health facility should do outreach services and adequate mobilization and sensitization through radios and resourceful people to bridge the knowledge gap on dental health care and utilization.